A VIETNAMESE- AMERICAN CROSS- CULTURAL STUDY ON CULTURE SHOCKS IN INTERMARRIAGE = Giao thoa văn hóa Việt Mỹ trên phương diện sốc văn hóa trong hôn nhân liên quốc gia - Lê, Thị Thanh Cầm (2020)
This thesis focuses on the culture shock problems of Vietnamese- American spouses. The objectives of the present study are to investigate: (i) the common types of culture shocks in Vietnamese- American intermarriage. (ii) the reasons and suggest some solutions for culture shock related problems. Problems and ways of solving culture differences in mixed- marriage are analyzed with data taken from the questionnaire for the Vietnamese and the English people. The first part of the questionnaire is personal information, and it was used to gather information of informants. The second part is ten multiple choice questions. They are designed to explore the common culture shock problems that people often argue. Also, it helps to check what people in intermarriage often do when they have culture difference problems relating to language, financial, points of view, custom and habits, etc. The results give out significant differences and similarities in the ways of dealing with difficulties in marriage life among Vietnamese and American couples. Besides, the author works out the seven common culture shock problems that people often have and also suggests some useful solutions for mixed- marriage spouses. More importantly, some contributions for implications for cross- cultural communication have been made so as to give the best knowledge for afterward learners and researchers. With the extremely essential role of the study, the author hopes to bring helpful findings for people concerning and give the best pleasure for readers to read it.